Cardiorespiratory Fitness and Mortality in Healthy Men and Women - Imboden, Mary T; Harber, Matthew P; Whaley, Mitchell H; Finch, W Holmes; Bishop, Derron L; Kaminsky, Leonard A (Journal of the American College of Cardiology, 2018)
There is a well-established inverse relationship between cardiorespiratory fitness (CRF) and mortality. However, this relationship has almost exclusively been studied using estimated CRF. This study aimed to assess the association of directly measured CRF, obtained using cardiopulmonary exercise (CPX) testing with all-cause, cardiovascular disease (CVD), and cancer mortality in apparently healthy men and women. Participants included 4,137 self-referred apparently healthy adults (2,326 men, 1,811 women; mean age: 42.8 ± 12.2 years) who underwent CPX testing to determine baseline CRF. Participants were followed for 24.2 ± 11.7 years (1.1 to 49.3 years) for mortality. Cox-proportional hazard models were performed to determine the relationship of CRF (ml·kg ·min ) and CRF level (low, moderate, and high) with mortality outcomes. During follow-up, 727 participants died (524 men, 203 women). CPX-derived CRF was inversely related to all-cause, CVD, and cancer mortality. Low CRF was associated with higher risk for all-cause (hazard ratio [HR]: 1.73; 95% confidence interval [CI]: 1.20 to 3.50), CVD (HR: 2.27; 95% CI: 1.20 to 3.49), and cancer (HR: 2.07; 95% CI: 1.18 to 3.36) mortality compared with high CRF. Further, each metabolic equivalent increment increase in CRF was associated with a 11.6%, 16.1%, and 14.0% reductions in all-cause, CVD, and cancer mortality, respectively. Given the prognostic ability of CPX-derived CRF for all-cause and disease-specific mortality outcomes, its use should be highly considered for apparently healthy populations as it may help to improve the efficacy of the individualized patient risk assessment and guide clinical decisions.